Drug Utilization Review on Non-Steroidal Anti-Inflammatory Drugs: Pharmaceutical Science-Pharmacy Practice for Good Health Promotion - Madhuri latha.thadanki; Ayesha ahmadi; K.Geetha mounika; V.Pravallika (International Journal of Life Science and Pharma Research, 2022)
In India, any prescription generally has an NSAID. According to our knowledge many of the studies were done on NSAID’s hence, the present study is carried out to know the usage and prescribing patterns of NSAID’s. The information generated from the study might be supportive to communicate with the prescribers and advice the various gaps noticed for improving the prescribing patterns for best patient outcomes, and the information also helps in outlining further studies. Thus it ultimately benefits the patients in minimizing the incidences of drug interactions with NSAID’s if any and adverse effects caused due to NSAID’s. The aim of the paper is to conduct a retrospective observational study in a tertiary care teaching hospital to assess demographic and clinical variables like drug interactions associated with NSAID administration, for the 6 months in all departments except Paediatrics. All patients of various age groups who have received NSAID’s therapy from all departments were included by giving pre-informed consent in our study. Prescribing patterns were observed and analyzed in 300 patients during the study period. Among 300, 162 were males and 138 were females. Out of all, 36 patients were from age group >70, 50 patients were from age 61-70, 51 patients from age 51-60, 49 patients from 41-50, 48 patients from 31-40, 56 patients from age 21-30 and 10 patients from age 11-20. A social history of every patient was collected and analyzed where 56 were smokers, 244 were non-smokers and 72 were alcoholics, 228 were non-alcoholics. Paracetamol was the most widely used drug of about 42%. We found 11.22% major drug interactions, 37.75% moderate interactions and 51% minor interactions. Statistical analysis one way ANOVA was done in SPSS version 21software, and the result was of significant difference between NSAID’s treatments. Two way ANOVA was done which showed variability in gender groups with treatment regard to NSAID’s is due to chance attributed to effects of gender or effect of treatment. Though many drugs are prescribed lucidly in India, not much differences are found in prescriptions given by healthcare professionals, and in prescribing patterns. To promote better patient compliance and to detect the adverse drug reactions early, involvement of clinical pharmacist helps more in prescribing the drugs rational.